18F-FDG PET/CT in a Patient With Malignant Pheochromocytoma Recurrence and Bone Metastasis After Operation—Case Report and Review of the Literature - Feng, Bei; Chen, Maojia; Jiang, Yanghongyan; Hui, Yongfeng; Zhao, Qian (Frontiers in Medicine, 2021)
Introduction: Bone metastasis of malignant pheochromocytoma is a rare disease. We report a patient with a 10-year history who underwent 18F-FDG PET/CT to detect bone metastasis and receive radiotherapy and chemotherapy with complete response for bilateral iliac pain. Case presentation: A 48-year-old male patient complained of dizziness, hypertension, and bilateral iliac pain for 2 months. The patient had a history of resection of bilateral malignant adrenal pheochromocytoma 10 years earlier, and all complaints were relieved immediately after operation. 18F-FDGPET/CT showed abdominal lymph node uptake and multiple bone uptake, as well as multiple brown fat uptake. A biopsy of the left ilium confirms the metastasis of malignant pheochromocytoma. Discussion: In our literature review, we discuss the metastasis of pheochromocytoma reported by some scholars, and the role of radionuclides such as 18F-FDG PET/CT, 18F-DOPA PET/CT, I-123MIBG, and 68Ga-DOTATATE PET, in the diagnosis of malignant pheochromocytoma. The patient above is a good case for clinicians in the diagnosis and treatment of metastatic pheochromocytoma, especially in some hospitals with only 18F-FDG imaging agents. Conclusion: A review of this case and similar rare cases in the literature illustrates the importance of 18F-FDG PET/CT in the diagnosis of malignant pheochromocytoma.